The Qur'an in the Modern Era: A Critical Analysis of Contemporary Interpretations - Bamba, Abdoulaye (Islamic Religious Education Departement, 2024)
The Qur'an, the sacred book of Muslims, is considered the primary source of divine knowledge and religion. It has been the subject of extensive study by scholars of various disciplines for decades. To preserve the faithful transmission of his teachings, strict rules have been established to which all scholars must conform.However, in recent decades, some works have emerged which are subject to inconsistency with the carefully established rules. In this article, we will focus on a critical and scientific approach to certain opinions and ideas formulated in the books of NICOLAÏ Sinai, entitled